Development of E-learning and Reflections of the Internet on the Process of Education: A Case Study at Gazi University - Mehmet Toplu; Şahin Gökçearslan (Türk Kütüphaneciliği)
Since the second half of the 20th century, the developments in the field of information technologies and the Internet have introduced significant changes in both traditional and distance learning and e-learning has become one of the fundamental elements of education. While e-learning and educational use of the Internet have been getting more common, higher education institutions have been reviewing and restructuring their own positions in line with the developments in these areas. Around 50 universities in Turkey started remote education programs. Furthermore new tools to promote face to face education continue to exist on the Internet and to increase the efficiency of the courses. Since the beginning of the second part of2000s, the Turkish Academy of Sciences (TÜBA) has been leading the work for the implementation of the project of open course materials in order to improve the effectiveness of face to face courses and it has been supported by a number of universities.